Association between sexual violence and unintended pregnancy among married women in Zambia - Mwewa E. Kasonde; Bwalya Bupe Bwalya; Elizabeth T. Nyirenda; Chabila Christopher Mapoma; Milika Sikaluzwe; Kafiswe Chimpinde; Gloria I. Songolo (BMC Public Health, 2022)
Abstract Background One of the outcomes of sexual violence is unintended pregnancy. In Zambia, 15% of married women age 15—49 years had experienced sexual violence from their husband or partner. The prevalence of unintended pregnancies among women age 15—49 years has risen from 33% in 1992 to 38% in 2018. The link between sexual violence and unintended pregnancy in Zambia was investigated in this study. Methods This study used the women's dataset from the 2018 Zambia Demographic and Health Survey, a cross-sectional survey. The study looked at a weighted sample size of 4,465 women age 15 – 49 years. Unintended pregnancy was measured by combining response categories of mistimed and unwanted pregnancy. Multivariate binary logistic regression was performed to establish the net effects of sexual violence and each explanatory variable on unintended pregnancy. Results The findings suggest that sexual violence does have a role in unintended pregnancies (AOR 1.74; CI 1.38—2.19). Ever use of contraception is also a significant predictor of unintended pregnancy (AOR 1.48; CI 1.16—1.88), even when other characteristics are taken into account. Results have shown that a woman who had ever used contraception and had experienced sexual violence was more likely to have an unintended pregnancy. Conclusion Spousal sexual violence is highly associated with unintended pregnancies in Zambia. Addressing intimate partner sexual violence is among the ways to prevent unintended pregnancies. It is also important to sensitize women on reporting acts of sexual violence to relevant authorities as this will not only prevent reoccurrence of sexual violence but also reduce unintended pregnancies and associated long-term effects.